1994
DOI: 10.1139/e94-147
|View full text |Cite
|
Sign up to set email alerts
|

Timing constraints on deformation history of the Sudbury Impact Structure

Abstract: Herein, we present new high-resolution seismic images of the Sudbury Impact Structure, acquired across the Sudbury Igneous Complex and its environs, which provide evidence for the relative timing of the deformation events that reshaped the initial Sudbury Structure. The seismic images show that the lower unit of the Sudbury basinal fill sediments, the Onwatin argillite, is penetrated by a set of blind, imbricated thrusts, whereas the overlying Chelmsford turbidites are unaffected by faulting. We interpret this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 16 publications
2
5
1
Order By: Relevance
“…The observed times were checked to ensure that a proper distance range was used in calculating the values of Vo. This interpretation is in general agreement with the interpretation based on seismic reflection study of Wu et al (1994). However, in contrat to their mode1 which showed that the SIC is well elongated to the south, we interpret that the SIC, more or less, mimics the basinal structure shown in Fig In fact, the observed similarities in the high frequency fluctuations pattern between the free-air and the Bouguer gravity further indicates that this high frequency component is mainly caused by the near surface disturbances and not due to the effect of terrane's topography.…”
Section: The Refraction Experimentssupporting
confidence: 91%
“…The observed times were checked to ensure that a proper distance range was used in calculating the values of Vo. This interpretation is in general agreement with the interpretation based on seismic reflection study of Wu et al (1994). However, in contrat to their mode1 which showed that the SIC is well elongated to the south, we interpret that the SIC, more or less, mimics the basinal structure shown in Fig In fact, the observed similarities in the high frequency fluctuations pattern between the free-air and the Bouguer gravity further indicates that this high frequency component is mainly caused by the near surface disturbances and not due to the effect of terrane's topography.…”
Section: The Refraction Experimentssupporting
confidence: 91%
“…A melt pond implies gravitational leveling, and is consistent with the observation that the composition (Naldrett, 1984) and isotopic signature of the SIC requires only contributions from crustal rocks (Grieve et al, 1991). Under this assumption, large-scale, non cylindrical folding may be the only means of obtaining a doubly plunging syncline exposing oblique sections through the thickness of the SIC (e.g., Cowan and Schwerdtner, 1994;Wu et al, 1994). This requirement for folding is not obviated by the structural mapping data that suggest some portion of the SIC might be intrusive (Cowan and Schwerdtner, 1997;Riller and Schwerdtner, 1997).…”
Section: Sudbury Igneous Complex Noritesupporting
confidence: 70%
“…Perhaps 40% of the Onaping compression occurred as layer parallel shortening prior to buckling and the formation of the SRSZ (Hirt et al, 1993). While the layer parallel shortening is not visible in the seismic data, Wu et al (1994) showed strong evidence that brittle thrust faulting offsets the contact between the Onwatin and Onaping Formations (Fig. 6).…”
Section: Sediments Of the Whitewater Groupmentioning
confidence: 97%
“…() used a single profile of the sparse local seismic reflection data to support the crater hypothesis. While seismic reflection data can identify large impact structures (Morgan et al., ; Osinski & Spray, ; Poag, , ; Poag, Hutchinson, Colman, & Lee, ; Scott & Hajnal, ; Stewart & Allen, ; Wu, Milkereit, & Boerner, ), we argue that the seismic data they presented do not corroborate the crater hypothesis. Typically, impact craters identified on seismic data have the following features (French, ; French & Koeberl, ), none of which are convincingly seen in the seismic data: modest downward and inward displacements of the rocks at the crater margin; a complex ring fault system; structural disruption in a central zone, with incoherent seismic reflectors and evidence of preserved and continuous reflectors at depth. …”
contrasting
confidence: 63%
“…Rocca et al (2017) used a single profile of the sparse local seismic reflection data to support the crater hypothesis. While seismic reflection data can identify large impact structures (Morgan et al, 1997;Osinski & Spray, 2005;Poag, 1996Poag, , 1997Poag, Hutchinson, Colman, & Lee, 1999;Scott & Hajnal, 1988;Stewart & Allen, 2005;Wu, Milkereit, & Boerner, 1994), we argue that the seismic data they presented do not corroborate the crater hypothesis. Typically, impact craters identified on seismic data have the following features (French, 1998;French & Koeberl, 2010), none of which are convincingly seen in the seismic data:…”
mentioning
confidence: 99%